ChemInform Abstract: Asymmetric Vinylogous Michael Reaction of Cyclic Enones with Silyloxy Furans. Issue 1 (17th December 2015) - Jadhav, Amol P.; Bhaskara Rao, V. U.; Singh, Pradeep; Gonnade, R. G.; Singh, Ravi P.
Abstract: The reaction of substituted cyclohexenones and 2‐silyloxyfurans delivers the corresponding Michael‐adducts in moderate to high yields and with very high diastereo‐ and enantioselectivity.